EVALUATION OF ANTIBACTERIAL EFFICACY OF CHEMICALLY SYNTHESIZED COPPER AND ZEROVALENT IRON NANOPARTICLES - SELVARANI, M.; PREMA, P. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: Growing resistance of microorganisms to potent antibiotics has renewed a great interest towards investigating bactericidal properties of nanoparticles and their nanocomposites as an alternative. Therefore, the present study has been carried out to investigate and compare the antibacterial properties of copper (Cu) and zerovalent iron (Feo) nanoparticles. Methods: Nanoparticles were synthesized by reducing aqueous solution of respective salt solution with sodium borohydride. The synthesized particles were further characterized by X-Ray Diffractogram (XRD), and Scanning Electron Microscopy (SEM) techniques to analyze size and morphology respectively. Antibacterial efficacy of metal nanoparticles was evaluated by agar well diffusion method. Results: Average size of the particles was found to be 17.25 nm (Cu) and 44.87 nm (Feo). Energy-dispersive spectrum (EDS) of the nanoparticles dispersion confirmed the presence of elemental metals. The mechanism of microorganism inactivation is considered species-dependent. Pseudomonas aeruginosa exhibited highest antibacterial sensitivity (26.00 Â± 0.41 mm) to copper nanoparticles whereas Bacillus cereus offered maximum zone of inhibition (23.33 Â± 0.89 mm) to Feo nanoparticles. Conclusion: Results from this study signify that the Cu and Feo nanoparticles potentiate the antibacterial action of both gram positive and gram negative bacteria.